1985
DOI: 10.1016/0014-5793(85)80279-9
|View full text |Cite
|
Sign up to set email alerts
|

1H‐NMR study of the interaction of aminopyrine with purified rat liver microsomal cytochrome P‐450

Abstract: Longitudinal relaxation (T 1) measurements for all lines (N(CH3)2, N(CH3), (C(CH3), phenyl) in the aminopyrine 1H‐NMR spectrum were used to study the interaction of aminopyrine with purified microsomal cytochrome P‐450 from livers of phenobarbital‐treated rats. The paramagnetic contribution to the observed t 1 −1 values was determined from its dependence on aminopyrine concentration. The Solomon‐Bloembergen equation was used to calculate between Fe3+ and aminopyrine distances in the enzyme‐substrate complex. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Estimation of the correlation time of the electron spin relaxation τ c ()τ s ; see Materials and Methods) was made by measuring the H 2 O protons' relaxation rate in the presence of CYP 2C9 at 250 and 500 MHz. This gave a value of 2 × 10 -10 s, which is an approximation well in the range of previously estimated τ s values for other P450s (Griffin & Peterson, 1975;Philson et al, 1979;Woldman et al, 1985;Modi et al, 1995), and very similar to that recently reported for another human liver P450, P450 2D6 (Modi et al, 1996). The fact that a water molecule is present or not on the coordination sphere of the iron when the substrate is present has been studied by the NMR measurements of the relaxation times of water on the free and tienilic acid bound CYP 2C9.…”
Section: Resultssupporting
confidence: 88%
“…Estimation of the correlation time of the electron spin relaxation τ c ()τ s ; see Materials and Methods) was made by measuring the H 2 O protons' relaxation rate in the presence of CYP 2C9 at 250 and 500 MHz. This gave a value of 2 × 10 -10 s, which is an approximation well in the range of previously estimated τ s values for other P450s (Griffin & Peterson, 1975;Philson et al, 1979;Woldman et al, 1985;Modi et al, 1995), and very similar to that recently reported for another human liver P450, P450 2D6 (Modi et al, 1996). The fact that a water molecule is present or not on the coordination sphere of the iron when the substrate is present has been studied by the NMR measurements of the relaxation times of water on the free and tienilic acid bound CYP 2C9.…”
Section: Resultssupporting
confidence: 88%
“…The NMR method has been used by Novak et al [4-S] to study the interaction of cytochrome P-450 with substrates such as acetanilide and xylidine, and by Woldman et al [7,8] with ligands such as uminopyrine and 4-methoxypyridine.…”
Section: Introductionmentioning
confidence: 99%